Security Everywhere Cloud: An Intensive Review of DoS and DDoS Attacks in Cloud Computing - Jaber, Aws Naser; Mohamad Fadli, Zolkipli; D. Ahmed, Firas D. Ahmed; Mazlina, Abdul Majid (Academic Research Online Publisher, 2015)
Distributed computing is a widely utilized approach for rapidly enhancing an organization’s information technology capabilities while minimizing additional resource requirements. It can efficiently and effectively broaden an organization’s existing IT competencies. In recent years, distributed computing has developed from being a novel and unfamiliar business idea into a rapidly expanding IT business sector. However, as additional organizations and individuals relocate their data and applications into the cloud, significant concerns are starting to develop regarding the infrastructure’s ability to protect sensitive data. Despite the considerable movement toward cloud-based computing, venture clients remain hesitant to relocate their business data into the cloud. Security has proved to be a significant issue, and those concerns continue to diminish the development of distributed computing